Investigation of asphalt aging behaviour due to oxidation using molecular dynamics simulation. Issue 8 (23rd May 2016) - Pan, Jielin; Tarefder, Rafiqul A.
Abstract: An attempt is made to connect the link between internal chemical and molecular mechanical property change and external physical, rheological and mechanical property change for asphalt before and after oxidative aging using molecular dynamics (MD) simulation. Intermolecular interactions, density, bulk modulus and zero shear viscosity changes of model asphalt systems before and after oxidative aging and mechanical property changes of the asphalt systems under different compressive and tensile stress rates are investigated at room temperature (298 K). Simulation results demonstrate that oxidised functional groups in asphalt molecules increase the strength of intermolecular bonds and the bulk modulus of asphalt, which further contribute to the hardening of the oxidised asphalt. The internal property change is consistent with the external physical and rheological property change after oxidation, which is revealed by the increase of density and viscosity. In addition, both the unoxidised and oxidised asphalts deform more and fail faster with an increase in both compressive and tensile stress rates, especially under tensile stresses. The oxidised asphalt is stiffer than the unoxidised asphalt, which shows less deformation.